Relationship Marketing and the Effect of Culture in the Business-to-Business Context- Focusing on the Garment Exporters in India - Grover, Tania (2006)
Abundance of research has taken place in the field of relationship marketing in recent years; however, the operational concepts of this paradigm are still unclear and require more investigation. This study attempts to contribute to the literature by examining the factors which play a significant role in the formation and development of relationships in the Indian garment export industry. It also takes a cross-cultural perspective and examines the perception of different countries in context to relationship marketing in the industrial sector. The opening chapter of this research consists of the relevant literature that has been comprehensively reviewed and discusses issues such as the emergence of relationship marketing, factors that lead to the formation of relationship marketing, formation of relationships in business-to-business markets and the effect of culture on relationships. For the purpose of this research qualitative research methodology has been chosen in order to satisfy the aims and objectives of this dissertation. The researcher has used 8 in-depth interviews to gather data in order to gain an understanding on this subject. Further on, the findings from the interviews have been analysed and discussed in context of the literature provided. Based on the interviews a number of new elements have been identified as significant factors which are considered important for the formation and development of relationships in the Indian export garment industry. Finally the limitations, recommendations and concluding thoughts of the research have been discussed.